Resilience against political and religious extremism, radicalization, and related violence: A systematic review of studies on protective factors - Lösel, Friedrich; Bender, Doris; Jugl, Irina; King, Sonja (Understanding Recruitment to Organized Crime and Terrorism, 2020)
Politically, islamist, or otherwise motivated extremism, radicalization, and violence are highly topical issues in many countries. Thousands of publications address theoretical concepts, potential origins, risk factors, developmental phases, and approaches to prevention. However, there is not yet much research with a focus on resilience and protective factors in this domain. This article contains a systematic review of quantitative studies that investigated protective effects against extremism and radicalization as well as qualitative research on factors that contribute to disengagement from radical groups. After screening more than 2,000 documents, we found 28 eligible reports containing 21 analyses that provided quantitative data and seven qualitative interview studies. Most studies addressed islamist (religious/ethnic) extremism, some others far-right, far-left, and mixed forms. Thirty different protective factors showed significant effects against radicalization. Replicated factors were self-control, adherence to law, acceptance of police legitimacy, illness, non-deviant significant others, positive parenting behavior, good school achievement, non-violent peers, contact to foreigners, and a basic attachment to society. The results of the qualitative research on disengagement were in accordance with some of these individual and social “pull factors” but also showed “push factors” like disillusionment and negative experiences in the radical group as well as critical reflections and identity changes. Many findings were similar to what we know from resilience against and desistance from violence in other fields. Therefore, issues of extremism, violent radicalization, and terrorism should become more integrated into criminology. Limitations of the systematic review and potential practical implications are discussed.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Extremism; Protective factors; Radicalization; Resilience; Systematic review; Terrorism